Funding, Organisational Factors and Quality Research Output in Colleges of Education in South-West, Nigeria - BELLO, Abiodun Eniola (International Journal of Educational Management, 2025)
This study investigated funding, organisational factors and quality research output in Colleges of Education in South-west, Nigeria. The study adopted the descriptive survey research of the ex-post facto type. The population of the study comprised of all 2,189 academic staff in the nine Colleges of Education in South-west, Nigeria. Proportionate sampling technique was used to select 30% of academic staff from the six purposively selected State and Federal Colleges of Education in Southwestern Nigeria. The data collected through researcher’s self-designed questionnaire titled ’Funding, Organisational Factors and Quality Research Output Questionnaire’ (FOFQROQ)’ were analyzed using pearson product moment correlation and multiple regressions. All the hypotheses were tested at 0.05 level of significance. The result from the analysis revealed that fund accessibility (r = 0.195, p<0.05) and working environment (r = 0.192, p<0.05) had significant relationship with quality research output in College of Education in South-west, Nigeria but leadership style (r = 0.070, p>0.05) had no significant relationship the quality research output. The study concluded that fund accessibility, working environment and leadership style could jointly influence the quality research output to some extent. It was therefore recommended that college management should ensure that the institutional based research grants are easily accessible by lecturers to carry out quality research and college management should create friendly and harmonious working environment for lecturers to carry out quality research.